Estimation of Genetic and Environmental Correlations between Age at First Calving and Production Traits with Reproduction Traits in Holstein Cows Using Bayesian Multi-Trait Model - Chegini, Arash; Safari, Abbas; Moridi, Misagh (My University, 2025)
The aim of the present study was to estimate heritability as well as genetic and environmental correlations between age at first calving (AFC) and production traits, namely 305-day milk yield (MY305), 305-day fat and protein yield (Fat305 and Pro305, respectively) and fat and protein percentage (Fat% and Pro%, respectively) with reproduction traits including calving to first heat (DFH), calving to first service (DFS), interval from first to last insemination (IFL), calving to conception interval (ICC), interval between two calvings (CI), number of inseminations (NIS), and conception rate at first insemination (CR) in Iranian Holstein. Records of 33,851 Holstein cows collected in five large dairy herds were used. The estimation of parameters was implemented by the Bayesian multi-trait linear and threshold animal and sire models. Heritability estimates were moderate for production traits and low for reproduction traits suggesting that the improvement of environmental conditions is necessary for improving reproduction traits. Genetic correlations between production and reproduction traits ranged from -0.46 (between Fat305 and CR) to 0.48 (between Fat305 and ICC) in animal model and from -0.55 (between Pro305 and CR) to 0.64 (between Fat305 and DFH) in sire model. Accurate estimates of genetic parameters can be used in selection plans in order to optimally select parents of the next generation.
Keywords: Bayesian multi-trait model; genetic correlation; age at first calving; days to first heat; calving interval; conception rate